ANALYSIS OF THE EFFECTIVENESS OF MARKETING MIX THROUGH SOCIAL MEDIA ON THE IMPULSIVE SPENDING BEHAVIOR OF ONLINE SLOT GAMBLING ADDICTS MEDIATED BY GAMBLING BEHAVIOR (CASE STUDY ON THE ACUTE GAMBLERS REHABILITATION TELEGRAM GROUP) - Teuku Roli Ilhamsyah Putra; Teuku Meldi Kesuma; Hizamrul Jaen (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research analyzes the effectiveness of Marketing Mix elements (product, price, place, promotion, personalization, privacy, customer service, community, site design) via social media on Impulsive Spending among online Slot gambling addicts in rehabilitation, mediated by Gambling Behaviour. Employing a quantitative method with a PLS-SEM approach, data were collected from 100 respondents, members of a Telegram acute gambler rehabilitation group, through questionnaires and interviews. The primary data comprised respondents' self-reported behavioural and financial information. Respondents were diverse adult individuals aware of gambling's negative impacts but strongly driven by internal motivations (such as recovering financial losses). Results indicate that most Marketing Mix elements do not significantly influence their compulsive Gambling Behaviour; gambling habits are primarily fueled by internal urges. However, promotion and personalization were found to have a significant and direct influence on triggering Impulsive Spending. Gambling Behaviour did not significantly affect Impulsive Spending and did not mediate the relationship between Marketing Mix and Impulsive Spending. Conclusion: In this population, internal drive dominates Gambling Behaviour, yet specific Marketing Mix tactics (promotion and personalization) remain effective in directly triggering Impulsive Spending. Keywords: Marketing Mix, Impulsive Spending, Gambling Behaviour, Online Slot Gambling, Rehabilitation